Chitosan hydrogel wrapped bimetallic nanoparticles based efficient catalysts for the catalytic removal of organic pollutants and hydrogen production. (31st May 2022) - Bakhsh, Esraa M.; Khan, Mohammad Sherjeel Javed; Akhtar, Kalsoom; Khan, Sher Bahadar; Asiri, Abdullah M.
Abstract : A novel catalytic system based on bimetallic nanoparticles entrapped chitosan hydrogel container (Cu–Ag/CH, Cu–Co/CH, Cu–Ni/CH) was prepared. The developed catalytic system was applied for production of H2 from water and methanol and reduction of 4‐nitrophenol (4‐NP), 3‐nitrophenol, 2‐nitrophenol, 2, 6‐dinitrophenol, methylene blue, congo red (CR), methyl orange, acridine orange, and potassium ferricynide (K3 [Fe(CN)6 ]). The developed catalytic system has shown tremendous performance and exhibited high efficiency as a catalyst for water treatment and H2 generation. Among all the nanocatalysts, Cu–Co/CH was more efficient in catalytic H2 generation while Cu–Ni/CH was more efficient in catalytic reduction of toxic contaminants. Further, various parameters like amount of NaBH4, catalyst quantity, pollutant concentration, and temperature were optimized to enhance the effectiveness of catalytic system for fast production of H2 and reduction of toxins. Moreover, the recyclability of the catalyst was investigated, where slight decrease in reduction time was noted. Abstract : Cu‐Co/CH, Cu‐Ni/CH based stable and recyclable catalytic systems were developed. Cu‐Co/CH was more efficient in catalytic H2 generation while Cu‐Ni/CH was more efficient in catalytic reduction of contaminants.